Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.2105/ajph.84.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neurological sequelae to organophosphate pesticide poisoning.

Abstract: OBJECTIVES. This work was undertaken to determine whether there are any chronic neurological sequelae to acute organophosphate pesticide poisoning. METHODS. California surveillance data were used in a study of neurological function among 128 men poisoned by organophosphate pesticides in California from 1982 to 1990 and 90 referents. Tests included a neurological physical examination, 5 nerve conduction tests, 2 vibrotactile sensitivity tests, 10 neurobehavioral tests, and 1 postural sway test. RESULTS. After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
1
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(159 citation statements)
references
References 11 publications
8
144
1
6
Order By: Relevance
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 83%
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 83%
“…Engel et al 42) observed that ulnar MCV in apple thinners who were exposed to detectable levels of organophosphorus did not significantly become slower than that in references. On the other hand, Steenland et al 27) reported significant trends of increased impairment with increased days of disability for peroneal MCV in organophosphorus poisoning cases. Ruijten et al 26) reported the relationship between organophosphorus pesticide exposure and decreasing median MCV and SCV, peroneal MCV, and Sural SCV.…”
Section: Discussionmentioning
confidence: 99%
“…slowed NCVs [25][26][27] , prolonged latencies of brain-evoked potentials 28) , and indicated abnormal pattern on postural sway assessment 29) . However, it has been unclear which of the methods is most sensitive to the effects of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate (OP) poisoned individuals have shown a consistent pattern of deficits when compared to a non-exposed or non-poisoned population on measures of motor speed and coordination, sustained attention, and information processing speed (Reidy, et al, 1992;Rosenstock, et al, 1991;Savage, et al, 1988;Steenland, et al, 1994;Wesseling, et al, 2002). Similarly, several studies have identified neurobehavioral effects in workers with longterm low-level exposure to pesticides.…”
Section: Neurobehavioral Effects Of Pesticide Exposurementioning
confidence: 99%